A first course in mathematical modeling - Giordano, Frank R. (Brooks/Cole Thomson Learning, 2003)
This text provides an introduction to the entire modeling process. Throughout the book, users practice key facets of modeling, including creative and empirical model construction, model analysis, and model research.